Osteopathic Manipulative Treatment of Back Pain and Related Symptoms during Pregnancy: A Randomized Controlled Trial - LICCIARDONE, John C. (2009)
OBJECTIVE: To study osteopathic manipulative treatment (OMT) of back pain and related symptoms during the third trimester of pregnancy. STUDY DESIGN: A randomized, placebo-controlled trial was conducted to compare usual obstetrical care (UOBC) and OMT (UOBC+OMT), UOBC and sham ultrasound treatment (UOBC+SUT), and UOBC only. Outcomes included average pain levels and the Roland Morris-Disability Questionnaire (RMDQ) to assess back-specific functioning. RESULTS: Intention-to-treat analyses included 144 subjects. The RMDQ scores worsened during pregnancy; however, back-specific functioning deteriorated significantly less in the UOBC+OMT group (effect size, 0.72; 95% CI, 0.31-1.14; P=.001 vs. UOBC only; and effect size, 0.35; 95% CI, −0.06-0.76; P=.09 vs. UOBC+SUT). During pregnancy, back pain decreased in the UOBC+OMT group, remained unchanged in the UOBC+SUT group, and increased in the UOBC only group, although no between-group difference achieved statistical significance. CONCLUSION: Osteopathic manipulative treatment slows or halts the deterioration of back-specific functioning during the third trimester of pregnancy.